(3LhGgQ GdYbOjf aj aVd GdTQajf TQa GdYde GdLdi hGdfSH GdYdis - (3Ydj Hf YHO Gddg GdMSjfj GdSeghOj GdTGaYjs
(3ChdgG (B:s
(3GdMeO ddg GdPi CYR ChdjGAg CYdGe GdOjf hbVi HhOge hMHge CeG HYO aEf Gddg ENJU YHGOg Cgd GdYde GdSfi , hCgd GdHjJ GdfHhi aGSJNQJ Gddg JYGdi ai JCdja QSGdI cGadI HYXje Mb gPjf GdTQajf s
(3BNQgG (B:s
(3aGdfUM ChLHg YdjfG QHfG ddcd ai SQ hai EYdGf bGd eDdag Yai Gddg Yfg hZaQ dg aQZJ ef JCdjag ai GdKGef ef QHjY GdKGfi YGe SHY hJSYjf hKeGfeGFI hGdMeO ddg hMOg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B614s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs